Bone volume–to–total volume ratio measured in trabecular bone by single‐sided NMR devices. Issue 1 (10th April 2017) - Brizi, Leonardo; Barbieri, Marco; Baruffaldi, Fabio; Bortolotti, Villiam; Fersini, Chiara; Liu, Huabing; Nogueira d'Eurydice, Marcel; Obruchkov, Sergei; Zong, Fangrong; Galvosas, Petrik; Fantazzini, Paola
Abstract : Purpose: Reduced bone strength is associated with a loss of bone mass, usually evaluated by dual‐energy X‐ray absorptiometry, although it is known that the bone microstructure also affects the bone strength. Here, a method is proposed to measure (in laboratory) the bone volume–to–total volume ratio by single‐sided NMR scanners, which is related to the microstructure of the trabecular bone. Methods: Three single‐sided scanners were used on animal bone samples. These low‐field, mobile, low‐cost devices are able to detect the NMR signal, regardless of the sample sizes, without the use of ionizing radiations, with the further advantage of signal localization offered by their intrinsic magnetic field gradients. Results: The performance of the different single‐sided scanners have been discussed. The results have been compared with bone volume–to–total volume ratio by micro CT and MRI, obtaining consistent values. Conclusions: Our results demonstrate the feasibility of the method for laboratory analyses, which are useful for measurements like porosity on bone specimens. This can be considered as the first step to develop an NMR method based on the use of a mobile single‐sided device, for the diagnosis of osteoporosis, through the acquisition of the signal from the appendicular skeleton, allowing for low‐cost, wide screening campaigns. Magn Reson Med 79:501–510, 2018. © 2017 International Society for Magnetic Resonance in Medicine.